DAMPAK PENENTUAN IURAN AIR DAN IPAIR (IURAN PELAYANAN AIR) TERHADAP POLA TANAM DAN PENDAPATAN PETANI - WIDHIANTHINI - (SOCA: Jurnal Sosial Ekonomi Pertanian, 2000)
Irrigation resource becomes more and more scarce. Apparently government hasn’tfund enough to finance operation and maintenance of irrigation system. Farmers are expectedto manage cost of operation and maintenance.The research is intended to show farmers’ response to water pricing and IPAIR thatinfluence the cropping pattern and income. Furthermore, Subak is expected to have capabilityto guarantee self financing, assignment and incentive system that are conform to theircapabilities.Data used in the research were obtained from a survey conducted at Subak Tegan inKapal, Badung District. The survey was done in three planting – July-October 1998;November 1998-February 1999; and March-Juny 1999. The cropping pattern in Subak Teganwas rice-rice-peanut and soybean. There were 56 farmers interviewed in the survey. The datawas analyzed by LINDO (Linear , Interactive and Discrete Optimizer).The results show that in condition of water price and IPAIR, maximum net income ofSubak Tegan decrease 0,26%-1,32% of first condition (non-water pricing and IPAIR). In thisresearch, Subak Tegan was assumed that it paid for IPAIR 100% (Rp 154.000,00/ha per yearand Rp 51.333,33/ha per planting season). The shadow price of water is zero. It means thatwater price belongs to be cheap. The price of rice and soybean (objective coefficient ranges)can rise, but peanut can’t. The product of rice and soybean (righthand side ranges) rise2.871,43 kg/ha for the first season, 2.873,21 kg/ha for the second and 1.028,22 kg/ha for thethird.The research concludes that the appropriate cropping pattern in Subak Tegan is ricerice-soybean. It is also recommended that the standard formulation of water pricing andIPAIR are very significant to create full autonomy of subak. They must conform to farmers’capability and irrigation system condition.